Homes Too Large for Household Needs? Under-Occupancy as Policy Problem and Lived Experience among Older Social Housing Tenants. Issue 1 (2nd January 2021) - Cheshire, Lynda; Forrest, Walter
ABSTRACT: Rising demand for social housing has induced housing authorities to find ways to increase the utilisation of existing housing stock, including targeting households thought to be living in homes that are larger than they need. This "under-occupation" of social housing is common among older tenants who, as with other under-occupiers, have been subject to unpopular measures designed to encourage downsizing. Yet little attention has been given to the housing needs of under-occupying older tenants and the ability of the social housing sector to meet those needs. In reviewing a new housing initiative for older under-occupying social housing tenants in Brisbane, Australia, this paper explores the housing needs and experience of this cohort. It shows that under-occupancy is a lived experience for some tenants and that downsizing to a smaller property is an attractive, albeit limited option. This suggests that policy prescriptions about the problem of older under-occupiers in the social housing sector should be reframed around the issue of tenants housing needs as they age.